1986
DOI: 10.1104/pp.81.2.329
|View full text |Cite
|
Sign up to set email alerts
|

A Temperature-Sensitive Chlorophyll b-Deficient Mutant of Sweetclover (Melilotus alba)

Abstract: The ch4 mutant of sweetclover (Melilotus alba) has previously been demonstrated to be partially deficient in chlorophyll and to have a higher ratio of chlorophyll a to b than normal plants. We were able to substantiate these findings when plants were grown at 23°C and lower (permissive temperatures). However, when grown at 26°C (nonpermissive temperature) the plants produced small yellow leaves which exhibited onetwentieth the chlorophyll content of normal plants. Affected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Very low or high temperatures in the growth environment may be detrimental to various metabolic processes, including Chl formation (Markwell et al, 1986). Lisar et al (2012) found that water stress inhibits chlorophyll synthesis, while carotenoids are less sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…Very low or high temperatures in the growth environment may be detrimental to various metabolic processes, including Chl formation (Markwell et al, 1986). Lisar et al (2012) found that water stress inhibits chlorophyll synthesis, while carotenoids are less sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies also revealed higher content of calcium and magnesium in the leaves at 25°C (Park and Oh 2000;Choi et al 2009). Very low or high temperatures in the growth environment may be detrimental to various metabolic processes in plant tissues, such as nutrient uptake, fluctuation in the anion exclusion volume and exchangeable Ca 2+ , chlorophyll formation and photosynthesis (Taylor and Rowley 1971;Rhee and Gotham 1981;Markwell et al 1986;Polubesova et al 1994). …”
Section: Resultsmentioning
confidence: 99%
“…However, few ofthese mutants have been characterized with regard to their specific biochemical defect. Although most such mutants have been grown under only one set of environmental conditions, a number of these mutants exhibit phenotypic plasticity in response to environmental variables such as temperature (4,8,9,12,16), photoperiod (1,5,9), and PPFD (7, 1 1).…”
Section: Methodsmentioning
confidence: 99%
“…However, few ofthese mutants have been characterized with regard to their specific biochemical defect. Although most such mutants have been grown under only one set of environmental conditions, a number of these mutants exhibit phenotypic plasticity in response to environmental variables such as temperature (4,8,9,12,16), photoperiod (1, 5, 9), and PPFD (7, 1 1).For the past few years, a portion of our work has focused on individuals from a collection of sweetclover (Melilotus alba) mutants (3,15,19) (18), was planted on a commercial soil-vermiculite mixture, incubated in a growth chamber at 26°C, 60% RH, 16 h photoperiod, and a PPFD of 250 to 400 ,umol m-2 s-', and supplemented weekly with a mineral salts solution (10). As the plants grew, individuals that subjectively appeared to have leaves of a lower Chl content than the normal A. thaliana Columbia ecotype were removed from the flats and grown in separate pots until seeds could be collected.…”
mentioning
confidence: 99%